1997
DOI: 10.1128/aac.41.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Use of a new mouse model of Acinetobacter baumannii pneumonia to evaluate the postantibiotic effect of imipenem

Abstract: Acinetobacter baumannii is responsible for severe nosocomial pneumonia. To evaluate new therapeutic regimens for infections due to multiresistant strains and to study the pharmacodynamic properties of various antibiotics, we developed an experimental mouse model of acute A. baumannii pneumonia. C3H/HeN mice rendered transiently neutropenic were infected intratracheally with 5 x 10(6) CFU of A. baumannii. The mean log10 CFU/g of lung homogenate (+/- the standard deviation) were 9 +/- 0.9, 9.4 +/- 0.8, 8.6 +/- 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 27 publications
3
70
0
Order By: Relevance
“…An initial indication about the protective role of neutrophils was the observation of high prevalence of infections caused by Acinetobacter in neutropenic patients (20). In agreement, early studies characterizing the therapeutic effect of imipenem against different strains of A. baumannii in a mouse model had to be performed in cyclophosphamide-treated neutropenic mice, due to the low susceptibility to A. baumannii shown by immunocompetent mice (21). Ten years later, van Faassen and colleagues directly evaluated the neutrophil role in pneumonia caused by A. baumannii .…”
Section: Neutrophils Essential Players During a Baumannii Infectionmentioning
confidence: 87%
“…An initial indication about the protective role of neutrophils was the observation of high prevalence of infections caused by Acinetobacter in neutropenic patients (20). In agreement, early studies characterizing the therapeutic effect of imipenem against different strains of A. baumannii in a mouse model had to be performed in cyclophosphamide-treated neutropenic mice, due to the low susceptibility to A. baumannii shown by immunocompetent mice (21). Ten years later, van Faassen and colleagues directly evaluated the neutrophil role in pneumonia caused by A. baumannii .…”
Section: Neutrophils Essential Players During a Baumannii Infectionmentioning
confidence: 87%
“…However, A. baumannii bacteremia spontaneously clears in mice unless a host defect is present [39]. Similarly, in our initial pilot experiments, a lethal iv infectious inoculum could not be identified in normal Balb/c mice, unless inocula were so high that they induced overwhelming infection resulting in death within 24 h (e.g., ≥10 9 bacilli).…”
Section: Resultsmentioning
confidence: 77%
“…In this model, results differ in accordance with inoculum density. In experimental models, A. baumannii leads to interstitial pneumonia [17,18]. Accordingly, in the current study the presence of interstitial pneumonia was demonstrated pathologically.…”
Section: Discussionmentioning
confidence: 89%
“…Increase in virulence of bacterial strains with porcine mucin or exacerbation of disease by creating neutropenia in animals were reported in various studies [1,8,19]. The virulence of A. baumannii does not differ among animals with or without neutropenia [18]. Most of the patients followed-up in our department are not neutropenic.…”
Section: Discussionmentioning
confidence: 90%